Perancangan Aplikasi Penjualan Menggunakan Metode Customer Relationship Managemen (CRM) Berbasis Web pada “CV Yosua Mandiri Grup” di Boyolali - Yohana Katharina Manurung; Fera Tri Wulandari; Wisnu Sanjaya (Universitas Boyolali, 2023)
In selling products the services provided are less effective because the services are obtained for customers who come to the location directly. Manual sales entrust and offer in several stores and pharmacies, and printing of monthly stock reports and sales reports are recorded in books and transferred to word documents. Services that are not strategic in meeting the needs of enthusiasts are due to the lack of two-way interaction, so the company cannot carry out sales activities and special services provided because of its limited range and lack of information media. Therefore it is necessary to build a website to facilitate sales, printing and apply the Customer Relationship Management (CRM) method as a strategy in business in approaching customer problems in improving service. The purpose of the website is to help online sales, so that it has a broad reach and can manage product and order data. Then the website as information liaison CRM with Whatsapp Business, as a form of strategy in improving services. In developing the system using the waterfall model, and computer language using PHP and MySQL database. The results obtained from this research are the website as a sales activity, and the CRM liaison by utilizing WhatsApp is done for personal interaction. Whapsapp is used as communication, for customers to talk to the company about their needs, complaints and asking questions. Then the benefit for the company is that it can find out customer needs, so that it can meet demand, in meeting needs a relationship can be formed. With WhatsApp, companies can offer special services to attract new customers and retain existing customers.